Left atrial diastasis strain slope is a marker of hemodynamic recovery in post-ST elevation myocardial infarction: the Laser Atherectomy for STemi, Pci Analysis with Scintigraphy Study (LAST-PASS) - Kato, Yoko; Lee, Wei Hao; Natsumeda, Makoto; Ambale-Venkatesh, Bharath; Takagi, Kensuke; Ikari, Yuji; Lima, Joao A. C. (Frontiers in Radiology, 2024)
Background Left atrial (LA) mechanics are strongly linked with left ventricular (LV) filling. The LA diastasis strain slope (LADSS), which spans between the passive and active LA emptying phases, may be a key indicator of the LA–LV interplay during diastole. Aim This study aimed to investigate the LA–LV interdependencies in post-ST elevation myocardial infarction (STEMI), with particular focus on the LADSS. Materials and methods Patients with post-anterior STEMI who received primary percutaneous coronary intervention underwent contrast cardiac magnetic resonance imaging (MRI) during acute (5–9 days post-STEMI) and chronic (at 6 months) phases. The LADSS was categorized into three groups: Groups 1, 2, and 3 representing positive, flat, and negative slopes, respectively. Cross-sectional correlates of LADSS Group 2 or 3 compared to Group 1 were identified, adjusting for demographics, LA indices, and with or without LV indices. The associations of acute phase LADSS with the recovery of LV ejection fraction (LVEF) and scar amount were investigated. Results Sixty-six acute phase (86.4% male, 63.1 ± 11.8 years) and 59 chronic phase cardiac MRI images were investigated. The distribution across LADSS Groups 1, 2, and 3 in the acute phase was 24.2%, 28.9%, and 47.0%, respectively, whereas in the chronic phase, it was 33.9%, 22.0%, and 44.1%, respectively. LADSS Group 3 demonstrated a higher heart rate than Group 1 in the acute phase (61.9 ± 8.7 vs. 73.5 ± 11.9 bpm, p < 0.01); lower LVEF (48.7 ± 8.6 vs. 41.8 ± 9.9%, p = 0.041) and weaker LA passive strain rate (SR) (−1.1 ± 0.4 vs. −0.7 [−1.2 to −0.6] s−1, p = 0.037) in the chronic phase. Chronic phase Group 3 exhibited weaker LA passive SR [relative risk ratio (RRR) = 8.8, p = 0.012] than Group 1 after adjusting for demographics and LA indices; lower LVEF (RRR = 0.85, p < 0.01), higher heart rate (RRR = 1.1, p = 0.070), and less likelihood of being male (RRR = 0.08, p = 0.058) after full adjustment. Acute phase LADSS Groups 2 and 3 predicted poor recovery of LVEF when adjusted for demographics and LA indices; LADSS Group 2 remained a predictor in the fully adjusted model (β = −5.8, p = 0.013). Conclusion The LADSS serves both as a marker of current LV hemodynamics and its recovery in post-anterior STEMI. The LADSS is an important index of LA–LV interdependency during diastole. Clinical Trial Registration https://clinicaltrials.gov/, identifier NCT03950310.